2016
DOI: 10.5350/dajpn2016290302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between drug compliance, coping with stress, and social support in patients with bipolar disorder

Abstract: Relationship between drug compliance, coping with stress, and social support in patients with bipolar disorder Objective: In bipolar disorder, recurrence rate is relatively high. With each episode, the risk of a new episode is increased. The first choice is drug treatment. However, patients have serious difficulties in drug compliance. This study was conducted to investigate drug compliance of patients with bipolar disorder, and to determine relationships between drug compliance, coping with stress, and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In the literature, studies investigating mental disorders and coping skills had different results. While some studies found that individuals with mental disorders use effective coping skills (Cohen, Hassamal, & Begum, ; Gloria & Steinhardt, ), the others found the use of ineffective coping skills (Adan, Antúnez, & Navarro, ; Aksoy & Kelleci, ; Mingrone et al., ; Moret‐Tatay, Beneyto‐Arrojo, Laborde‐Bois, Martínez‐Rubio, & Senent‐Capuz, ). In another study, it was determined that both methods were used together (Shrestha, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies investigating mental disorders and coping skills had different results. While some studies found that individuals with mental disorders use effective coping skills (Cohen, Hassamal, & Begum, ; Gloria & Steinhardt, ), the others found the use of ineffective coping skills (Adan, Antúnez, & Navarro, ; Aksoy & Kelleci, ; Mingrone et al., ; Moret‐Tatay, Beneyto‐Arrojo, Laborde‐Bois, Martínez‐Rubio, & Senent‐Capuz, ). In another study, it was determined that both methods were used together (Shrestha, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported that social support and interaction between the patients and their families increase adherence to treatment [11,12]. Adequate and improved social support positively affects the patients’ medication adherence and treatment, accelerates the treatment process, and improves the patients’ quality of life [13]. In the treatment of high blood pressure, it is necessary to understand the patients’ perspectives on medication adherence because high blood pressure has a silent and asymptomatic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Aldebot et al [33] reported that that a greater denial in coping is associated with a poorer medication adherence in schizophrenia. A study by Aksoy et al [34] revealed that patients with bipolar disorders preferring passive coping ways have smaller drug compliance rates. Also, de Brito et al [35], who thoroughly studied patients with renal grafts taking immunosuppressants, proved that the use of palliative coping pattern (religion/fantasy thoughts and emotion -focused coping) was associated with a non-adherence in those patients.…”
Section: Discussionmentioning
confidence: 99%